Peran Strategis Kaum Perempuan dalam Mewujudkan Masyarakat Religi - Achmad Syarifuddin (An Nisa'a, 2017)
This article explains about the position of Gender in an Islamic perspective and the role of women in the pursue and develop a generation that have a strong soul, great thinking and behavior that is dignified in the life of society, nation and State.Through the study of concepts and the results of the study of some researchers who have been dipublis through journals, both national and international writers gain an overview that Gender equality is not equal rights over men and women because each has its own characteristics. But more meaningful Gender Justice, equality inherent in every employee without having to see the gender (male or sister). While the role of each in creating the development community can be taken by men and women. Islam is very appreciative of women, likewise against males. If the man is a leader (qawwamuna) over women, but heaven is located on women. To the extent that the Prophet gave illustrations of the 3:1 (three as opposed to one) among women with men in terms of the means to a child. Thus, the perception that on behalf of religion to oppress women is a big mistake.